Selective Distribution Restrictions in the EU Competition Law - Daria Kostecka-Jurczyk (LeXonomica, 2020)
The dynamic development of digital technologies favours the rapid increase the popularity of electronic commerce, but at the same time causes an ever-stronger competitive pressure, prompting manufacturers and wholesalers to use various tools for controlling the sales system, especially prices. They often impose various restrictions on commercial partners (e.g. distributors) by preventing them from using certain sales channels. However, it is difficult to delimit the legality of such sales restrictions. It is very difficult to find an answer to the question of where the appropriate demarcation line should be drawn that determines the violation of competition rules, especially in online sales. Regulation 330/2010 seems not to be tailored to the assessment of restrictions in online distribution channels. The aim of the article is to point out the lack of appropriate tools to assess the restrictions of internet sales. The article shows that there is currently no uniform approach by antitrust authorities, which in turn results in legal uncertainty. It seems that the amendment of Regulation 330/2010 should be considered and the market share threshold set out in it should be lowered, while at the same time ensuring that it will be an actual safe harbour for companies, including online distributors.